Physical, Functional and Genetic Interactions between the BEACH Domain Protein SPIRRIG and LIP5 and SKD1 and Its Role in Endosomal Trafficking to the Vacuole in Arabidopsis - Steffens, Alexandra; Jakoby, Marc; Hülskamp, Martin (Frontiers in Plant Science, 2017)
Beige and Chediak Higashi (BEACH) domain-containing proteins (BDCPs) are facilitators of membrane-dependent cellular processes in eukaryotes. Mutations in BDCPs cause malfunctions of endosomal compartments in various cell types. Recently, the molecular analysis of the BDCP homolog gene SPIRRIG (SPI) has revealed a molecular function in P-bodies and the regulation of RNA stability. We therefore aimed to analyze, whether SPI has also a role in membrane-dependent processes. In this study, we show that SPI physically interacts with endosomal sorting complex required for transport associated ATPase Suppressor of K+-transport growth defect1 (SKD1) and its positive regulator, LYST Interacting Protein 5 (LIP5) and report genetic interactions between SPI and SKD1 and LIP5. We further show that the endosomal transport route of soluble proteins to the lytic vacuole is disturbed in spi lip5 double mutants but not in the single mutants. These vacuolar transport defects were suppressed by additional expression of SKD1. Our results indicate that the BEACH domain protein SPI has in addition to a role in P-bodies a function in endosomal transport routes.